Goal Recognition Design - Keren, Sarah; Gal, Avigdor; Karpas, Erez (Proceedings of the International Conference on Automated Planning and Scheduling, 2014)
We propose a new problem we refer to as goal recognitiondesign (grd), in which we take a domain theory and a set ofgoals and ask the following questions: to what extent do theactions performed by an agent within the model reveal its objective, and what is the best way to modify a model so thatany agent acting in the model reveals its objective as early aspossible. Our contribution is the introduction of a new measure we call worst case distinctiveness (wcd) with which weassess a grd model. The wcd represents the maximal lengthof a prefix of an optimal path an agent may take within a system before it becomes clear at which goal it is aiming. Tomodel and solve the grd problem we choose to use the models and tools from the closely related field of automated planning. We present two methods for calculating the wcd of agrd model, one of which is based on a novel compilation to aclassical planning problem. We then propose a way to reducethe wcd of a model by limiting the set of available actions anagent can perform and provide a method for calculating theoptimal set of actions to be removed from the model. Our empirical evaluation shows the proposed solution to be effectivein computing and minimizing wcd.